1980
DOI: 10.1515/znc-1980-9-1017
|View full text |Cite
|
Sign up to set email alerts
|

Light Diffraction of in vitro Crystals of Six Tobacco Mosaic Viruses

Abstract: Iridescent gels of the common, tomato mosaic, para-tobacco mosaic, ribgrass mosaic, sunnhemp mosaic, and cucumber 4 tobacco mosaic virus strains were prepared using the purification method of Boedtker and Simmons (J. Amer. Chem. Soc. 1958). Macrocrystals which were stable for many months could be grown from iridescent gels of all viruses when stored at 0-10 °C. The gels exhibited various structural phases (nematic and smectic) differing in density. The structure of the microcrystalline gels and of macrocrystal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
45
0
1

Year Published

1985
1985
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 0 publications
2
45
0
1
Order By: Relevance
“…19, No. 8,1986 that one has to integrate the exponent in eq 44 from x = D to a, which yields B2,el(sin $) = 2L2 sin $Jm(l -e-w/kBT) dx = (44) as can be seen from eq 1. Here, x is the shortest distance between the lines and 4 is the angle between them. In a calculation of the electrostatic excluded volume we stress This expression which holds for A' 2 2 has been used in eq 2.…”
Section: Relation Between Electrostatic Potential and Polyelectrolmentioning
confidence: 99%
See 1 more Smart Citation
“…19, No. 8,1986 that one has to integrate the exponent in eq 44 from x = D to a, which yields B2,el(sin $) = 2L2 sin $Jm(l -e-w/kBT) dx = (44) as can be seen from eq 1. Here, x is the shortest distance between the lines and 4 is the angle between them. In a calculation of the electrostatic excluded volume we stress This expression which holds for A' 2 2 has been used in eq 2.…”
Section: Relation Between Electrostatic Potential and Polyelectrolmentioning
confidence: 99%
“…Introducing the effective diameter Deff = D ( l + 6) (7) and the effective excluded volume (8) 4 we can write the free energy in the isotropic phase as beff = ZLZDeff…”
mentioning
confidence: 99%
“…Onsager also showed that the particle shape alone is enough to induce such behaviour. Moreover, at a later stage, it was found that rodlike colloids show the nematic-to-smectic-A phase transition, as in the case of TMV [8,9], fd virus [10][11][12] and β-FeOOH [13]. A detailed a e-mail: h.n.w.lekkerkerker@chem.uu.nl description of this phase transition came with theory [14][15][16][17][18] and computer simulations [19,20], showing that hardcore interactions are enough to induce such ordering.…”
Section: Introductionmentioning
confidence: 99%
“…In the 1950s, Oster 14 reported on an I-N biphasic suspension of tobacco mosaic virus rods that developed a third ͑Smectic-A) phase on the bottom of the sample after some time, an observation that was later confirmed by Kreibig and Wetter. 15 In neither case, a quantitative analysis was performed. Brian, Frisch, and Lerman 16 investigated sedimented suspensions of DNA-fragments at high salt concentration and analyzed their results in terms of a scaled particle theory equation of state.…”
Section: Introductionmentioning
confidence: 99%